Learning English as a Second Language: Approaches, Challenges, and Cultural Implications - Shakarboyev Mehriddin (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Learning English as a second language (ESL) is increasingly essential for global communication and integration, with English serving as the primary or secondary language in many countries worldwide. Mastering English offers numerous advantages, from greater career opportunities to enhanced cultural awareness. As technology advances and global citizenship takes on new significance, blended learning models and cultural integration have become central to ESL education. This article explores effective strategies, the benefits of cultural awareness, and the persistent challenges faced by ESL learners today.